PENGARUH FAKTOR EKSPOSI DAN TEBAL FANTOM TERHADAP MEAN GLANDULAR DOSE (MGD) PADA PESAWAT SINAR-X MAMMOGRAFI - Rauf, Resmy Aulyah; Astuty, Sri Dewi; Dewang, Syamsir; Mulyadin, Mulyadin (BERKALA FISIKA, 2020)
One of the applications of X rays in diagnostic radiology is mammography. The mammography is  used  for  detecting  abnormalities  in  the  breast  tissue  early  with  the  ability  to  detect microcalcification  (<5  mm).  Unlike  the  conventional  X-ray  and  CT  scanner,  the  clinical mammography  uses  a  low  voltage  <35  kVp,  because  the  properties  of  the  breast  tissue structures are soft and thin. Although the tube voltage source is relatively low, in clinical use, the absorbed dose by patients in the form of mean glandular dose (MGD) must  be lower than the  value  standards  had  been  established  by  the  Nuclear  Energy  Supervisory  Agency (BAPETEN) No.2, 2018, i.e <3 mGy. This study aims to evaluate the effect of variations in the values of the tube voltage, the current-time, and the thickness of the polymethyl-methacrylate (PMMA) phantom on the calculation results of the MGD values. The results obtained showed that  the  mean  MGD  values  for  the  4,5  cm  of  the  phantom  thickness  were  0.077, 0.087,  and 0.093  mGy  (at  4.5  mAs)  and  0.171,  0.194,  and  0.207  mGy  (at  10  mAs),  while  for  the  6  cm phantom thickness obtained 0.103, 0.117, and 0.124 mGy (at 4.5 mAs) and 0.228, 0.259, and 0.276 (at 10 mAs) for all the data to 27, 28, and 29 kVp of tube voltage, respectively. All of the MGD values obtained about between 0.077-0.276 mGy are <3 mGy or still under BAPETEN standards.Keywords: mammography, MGD value, PMMA phantom